Divided Nations and European Integration - Mabry, Tristan James (Book collections on Project MUSE., 2013)
Divided Nations and European Integration is a timely and authoritative collection that demonstrates how the expansion of pan-European institutions is affecting nations divided by sovereign borders, affording political opportunities to some but denying the aspirations of others.